Islamic Boarding School Leadership in Growing the Character of Love for the Motherland at Maqnaul Ulum Boarding School Sukowono Jember (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Abstract: This paper aims to describe Islamic Boarding School Leadership in fostering the character of love for the motherland. Islamic boarding schools were founded with the principle of kinship so that all models of pesantren leadership are still centralized, collective, innovative and traditional. kiai as the absolute leader in the pesantren environment. This research uses qualitative, case study type, data collection techniques using three techniques namely observation, interviews, and documentation using descriptive analysis with the interactive model of Miles, Huberman and Johnny Saldana namely data condensation, data display and drawing and verifying conclusions. First research results; The pesantren's leadership strategy, the ceremony on the 17th of each month, commemorating heroes' day, requires all students to take part in scouting training activities, kepaskibrakaan as a pesantren extracurricular activity. Second; Implementation of the leadership of the pesantren, Kiai and Ustadz-Ustadzah provided an exemplary spirit of Nationalism, Patriotism and high discipline, upheld the honor of all social life in the Islamic boarding school, carried out a competition for making a documentary film with the theme of veterans of the Republic of Indonesia's independence fighters, namely the figure of the founder of Islamic boarding school KH. Ahmad Nahrowi, scouting training, kepaskibrakaan which is followed by all students. Third; The contribution of the pesantren leadership, providing space and time for all students to think and be creative in a broad and advanced manner based on Islamic teachings according to the times, in embodying the character of love for the motherland at the Maqna’ul Ulum Islamic boarding school.